Optimization of roselle (Hibiscus sabdariffa Linn.) anthocyanin extraction parameter by response surface modeling and potential of roselle agro-waste as alternative sources of anthocyanin - Nurul Nadiah Abu Bakar,; Jalifah Latip,; Syaifuzah Sapian,; Rozida Mohd Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Roselle or Hibiscus sabdariffa Linn. is a perennial plant with a high concentration of anthocyanin in the calyx. This study optimized the extraction conditions for maximum anthocyanin yield in the calyx using response surface methodology (RSM) and face-centered central composite design (FCCCD), which showed that ultrasound-assisted extraction (UAE) method with 70% ethanol concentration (v/v) at 35 minutes had the highest total anthocyanin content (TAC) which at 5.277 mg Cya3G/g DW. Using this optimised extraction method, roselle agro-waste which are calyx residue, leaf and stem were extracted and tested for TAC. The highest TAC was found in the calyx residue (3.011 mg Cya3G/g DW), followed by stems (0.077 mg Cya3G/g DW), and leaves (0.073 mg Cya3G/g DW). This study also quantified the concentration of two major anthocyanins using high-performance liquid chromatography (HPLC) and compared the total phenolic content (TPC) and total flavonoid content (TFC) of calyx and calyx residue extracts. Our findings showed that the TAC of calyx residue extracts was significantly low compared to calyx extracts. However, there were no significant differences in the TPC and TFC values. These results suggest that calyx residue, which is typically discarded after processing of calyx products, is a good source of phenolics and flavonoids and compatible with fresh calyx. In addition, calyx residues are still a good source of anthocyanins, making it an added-value for the roselle industry.